2017
DOI: 10.1371/journal.pone.0181851
|View full text |Cite
|
Sign up to set email alerts
|

Applying time-frequency analysis to assess cerebral autoregulation during hypercapnia

Abstract: ObjectiveClassic methods for assessing cerebral autoregulation involve a transfer function analysis performed using the Fourier transform to quantify relationship between fluctuations in arterial blood pressure (ABP) and cerebral blood flow velocity (CBFV). This approach usually assumes the signals and the system to be stationary. Such an presumption is restrictive and may lead to unreliable results. The aim of this study is to present an alternative method that accounts for intrinsic non-stationarity of cereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 65 publications
(120 reference statements)
0
35
0
Order By: Relevance
“…; Panerai, ), there is motivation to perform more sophisticated analyses to quantify the coupling mechanism of ABP and CBF (Placek et al . ). The wavelet transform method is a powerful mathematical tool for analysing intermittent, noisy and non‐stationary signals, such as measured in studies of the autonomic nervous system (Pichot et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Panerai, ), there is motivation to perform more sophisticated analyses to quantify the coupling mechanism of ABP and CBF (Placek et al . ). The wavelet transform method is a powerful mathematical tool for analysing intermittent, noisy and non‐stationary signals, such as measured in studies of the autonomic nervous system (Pichot et al .…”
Section: Introductionmentioning
confidence: 97%
“…With the clarification of the non-stationarity and non-linearity of CA (Panerai et al 1999;Panerai, 2014), there is motivation to perform more sophisticated analyses to quantify the coupling mechanism of ABP and CBF (Placek et al 2017). The wavelet transform method is a powerful mathematical tool for analysing intermittent, noisy and non-stationary signals, such as measured in studies of the autonomic nervous system (Pichot et al 1999;Addison, 2002;Davrath et al 2003;Keissar et al 2009), making it also a natural candidate for assessing cerebral pressure reactivity (Bishop et al 2012;Garg et al 2014;Tian et al 2016;Wszedybyl-Winklewska et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…With TF estimates we used strict linear modeling to assess the relationship between BP and CBFV. This kept nonlinear and nonstationary aspects of the system unconsidered (Castro et al 2017, Giller and Mueller 2003, Placek et al 2017. All nonlinear approaches showed that the coefficient of variance as a sign of the models quality or analog measures become smaller compared to the strict linear models indicating that these models were likely more precise.…”
Section: Our Study Has Limitationsmentioning
confidence: 98%
“…However, in terms phase, gain or impulse response as measure of comparison such models did not exhibit large differences from linear differential equations models (Kouchakpour et al 2014, Marmarelis et al 2014, Meel-van den Abeelen et al 2014, Panerai 1999a, Smirl et al 2015, Panerai et al 2001. Regarding non-stationarity present in the data, recordings over time periods of several minutes can average out non-stationary effects with the result that time-variant models and time-invariant models produce close results (Kouchakpour et al 2010, Marmarelis et al 2014, Nikolic et al 2015, Placek et al 2017.…”
Section: Our Study Has Limitationsmentioning
confidence: 99%
“…Parameters derived from the wavelet transform of ICP signals, like wavelet entropy (WE) and wavelet turbulence (WT), have been also used to study signal irregularity and variability in ICP recordings obtained during ITs [24]. Alternative time-frequency representations, such as Zhao-Atlas-Marks distribution, have been used to analyse cerebral autoregulation in healthy subjects during hypercapnia [25].…”
Section: Introductionmentioning
confidence: 99%